Six-Phase Electric Machines - Buksnaitis, Jonas Juozas (Springer International Publishing, 2018)
This book presents the design methodology and electrical diagrams of symmetrical six-phase windings, the main elements of the six-phase electrical machines that are being developed to help meet the demand for high power electric drive systems that are resilient and energy efficient. Chapters are fully illustrated and include detailed tables that provide a comprehensive analysis of energy exchange processes ranging from electrical to magnetic and reveal the advantages of such windings against analogical three-phase windings. .